2014
DOI: 10.3892/or.2014.3342
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin sensitizes glioblastoma to temozolomide by simultaneously generating ROS and disrupting AKT/mTOR signaling

Abstract: Temozolomide (TMZ), a DNA alkylating agent, represents the most important chemotherapeutic option for the treatment of glioblastoma in the clinic. Despite its frequent use, the therapeutic efficacy of TMZ remains very limited due to its frequent resistance in glioblastoma. Previous evidence suggested that curcumin (CUM), an ingredient of the Indian spice turmeric, is able to sensitize glioblastoma to TMZ treatment. However, the underlying molecular mechanism remains elusive. In the present study, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 29 publications
3
63
1
1
Order By: Relevance
“…Moreover, the cell protective autophagy has been reported to contribute to TMZ-induced cell death (40). The production of ROS and the disruption of AKT/mTOR signal have been demonstrated to contribute to the TMZ resistance (41). In this study, we focused on the contribution of TMZ-inducible ROS upregulation and the maintainable cysteine pool and GSH synthesis by xCT transporting and transsulfuration pathway in the resistance to TMZ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cell protective autophagy has been reported to contribute to TMZ-induced cell death (40). The production of ROS and the disruption of AKT/mTOR signal have been demonstrated to contribute to the TMZ resistance (41). In this study, we focused on the contribution of TMZ-inducible ROS upregulation and the maintainable cysteine pool and GSH synthesis by xCT transporting and transsulfuration pathway in the resistance to TMZ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin sensitizes the glioblastoma to temozolomide by simultaneously generating ROS and inhibiting Akt/mTOR signalling pathway (Yin et al, 2014). It also inhibits beta-amyloid (Aβ) aggregation and induces autophagy by down-regulating PI3K/Akt/mTOR signaling pathway.…”
Section: Mtormentioning
confidence: 99%
“…As the most effective medicine for malignant gliomas, the cytotoxicity of TMZ induced glioma cells apoptosis and activated multiple signaling pathway increasing glioma cells damages [43][44][45] . It has been reported that TMZ promoted ROS production in glioma tissues [46][47][48] . Our results indicated miR-144 had no effect on glioma cells apoptosis without other treatment.…”
Section: Discussionmentioning
confidence: 98%